Giant brain aneurysm in a two–year–old girl - Prastiya Indra G; Hapsari Kusumawardani; Darto Saharso (Paediatrica Indonesiana, 2010)
Brain aneurysm is an abnormal outward bulging of one of the brain arteries. Brain aneurysms are often discovered when they rupture, causing bleeding into the brain or the space surrounding the brain called the subarachnoid space. This subarachnoid hemorrhage can lead to hemorrhagic stroke, brain damage and death.1The aneurysm can present in all ages, but mainly after 50 year of age (ages 35 – 60), and exists a greater predisposition in females, with a ratio 3:2.2 Intracranial aneurysms in children are rare. About 0.5-4.6% of all aneurysms in children distinctly differ from adult, especially in male (2:1 to 3:1).3,4,5,6These injuries are located mainly in any cerebral artery specifically in those related to the well-known Circles of Willis such as internal carotid, middle cerebral and anterior cerebral artery as well as anterior communicating artery that corresponds to anterior circulatory circuit. In the posterior region they can be observed above the posterior cerebral artery, vertebral and basilar arteries, mainly. Aneurysm in children is mostly located at the bifurcation of ICA or vertebra-basilar artery posterior circulation, yet disproportionately with high incidence of posterior circulation aneurysm (40-50%) and of giant aneurysm (30-45%)